EFEKTIFITAS PENERAPAN SANKSI HUKUM TERHADAP PERSAINGAN CURANG DALAM PELELANGAN PEKERJAAN DI KOTA PALU - Osgar S Matompo (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
Economic development and progress of development in various sectors, including the business tends to influence the growing public interest in establishing the company. The maximum value of the work that can be done every company is adjusted to the level of qualification of its capabilities. In practice, the imposition of severe legal sanctions to businesses that commit unfair competition is expected to lead to a sense of a deterrent so that the businessmen will not repeat the offense and other businesses will be afraid to do similar acts. Keywords :The Application of Legal Sanctions and Unfair Competition.